Quality Assessment and Authentication of Raw Honey-Available at Local Markets of Punjab - Kausar, Ghazala; Ahmad Ibne Yousaf; Afzal, Umair; Tariq, Waqas; Ambreen, Mehwish; Gull, Zartasha; Hussain, Azzah Khadim; Khan, Saif Ullah (Indus Journal of Bioscience Research, 2024)
Honey have delightful sweetness, propitious nutrition, antioxidant, bioactive, viscous golden yellow substances and used widely in food, beverages, medicinal research against treatment of a number of infections caused by microbes (bacteria, viruses, and parasites) due to antifungal and antibacterial properties and its complex carbohydrates, vitamins, minerals, organic acids, phenolic compounds and anti-oxidants nature. Aim of this study was to identify adulteration in honey samples collected from local stores of different regions of Punjab, Pakistan. Seven honey samples were procured and analyzed for hydroxyl methyl furfural (HMF) contents, moisture content, protein contents, pollens, ash contents, total sugar contents (sucrose, non-reducing and reducing), viscosity, total soluble solids, pH, acidity and electrical conductivity. Results ranged for moisture contents from 19.97 to 25.6%, total soluble solids (TSS) ranged from 74.4 to 80, pH 2.4-4, protein contents from 0.29 to 0.44%, ash contents from 0.15 to 0.45%, pollens from 22.4 to 74.7, viscosity from 376.7 to 1030cP/s, total acidity from 17 to 41.9 meq/kg, total sugars from 66.2 to 78.2%, reducing sugars from 58.4 to 72.3%, non-reducing sugars from 4.6 to 8.8% and HMF contents ranged from 15.7-35mg/kg. Higher amount of HMF present in honey is the indication of heating and lower quality honey. The results were associated with standards and specifications of “Pakistan Pure Food Rules”. 40% samples did not meet criteria. The accurate quantification should employ for production of high quality honey with strict national legislations and monitoring on apiculture to avoid mixing of adulterants in honey.